2021
DOI: 10.1017/qpb.2021.3
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsisembryo as a quantifiable model for studying pattern formation

Abstract: Phenotypic diversity of flowering plants stems from common basic features of the plant body pattern with well-defined body axes, organs and tissue organisation. Cell division and cell specification are the two processes that underlie the formation of a body pattern. As plant cells are encased into their cellulosic walls, directional cell division through precise positioning of division plane is crucial for shaping plant morphology. Since many plant cells are pluripotent, their fate establishment is influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 158 publications
(203 reference statements)
0
3
0
Order By: Relevance
“…In cell-walled organisms, there are several examples of envelopes that surround the embryo and maintain its mechanical balance. In Arabidopsis, a recent study reported a transient proteinaceous envelope around early globular-stage embryo (Harnvanichvech et al, 2023). It is thought to control the outward mechanical forces exerted by cell turgor in embryo cells, that escapes the control of the surrounding endosperm, which is deflating at that stage.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-walled organisms, there are several examples of envelopes that surround the embryo and maintain its mechanical balance. In Arabidopsis, a recent study reported a transient proteinaceous envelope around early globular-stage embryo (Harnvanichvech et al, 2023). It is thought to control the outward mechanical forces exerted by cell turgor in embryo cells, that escapes the control of the surrounding endosperm, which is deflating at that stage.…”
Section: Discussionmentioning
confidence: 99%
“…Second, given the likely crosslinked proteinaceous nature of the envelope, the envelope could also serve a mechanical role. Plant developmental processes, in particular tissue patterning -which is crucial during embryogenesis (Palovaara et al, 2017;Harnvanichvech et al, 2021;Dresselhaus & Jurgens, 2021) -require a precise balance between outward directed osmotic forces, which are usually counterbalanced by tensile stresses in the stiff plant cell walls . In early stages of embryogenesis, cell walls need to accommodate substantial growth and thus need to be plastic and malleable (Malinowski& Filipecki, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Following the minimal surface area, the nucleus and thus shortest cell division plane is positioned in the geometrical center of the cell, creating a symmetrical division (van Dop et al, 2015;Yoshida et al, 2014). However, plant cells can also disobey the minimal surface area rule, resulting in asymmetric division with daughter cells of unequal volumes and different cell fates (Harnvanichvech et al, 2021;Ramalho et al, 2022;Yoshida et al, 2014). In the B. napus and Arabidopsis zygotic embryo, the first division of the zygote is asymmetric, giving rise to two daughter cells with different fates .…”
Section: Cell Division Plane and Cell Fatementioning
confidence: 99%